(untitled) (E Global Congress, 2023)
The current development of the technique is characterized by a large consumption of energy, and therefore is the period of the scientific and technological revolution, differing in quality level from previous developments. The level of quality is primarily manifested in large revolutionary shifts of the production forces in labor weapons equipped with highly efficient automation in a wide range. Therefore, nowadays, the achievement of energy efficiency at the expense of eliminating losses in the power supply systems of industrial enterprises has become one of the pressing problems. For this reason, the dissertation work is considered relevant.